KREATIVITAS GURU KETRAMPILAN DALAM MENGATASI KETERBATASAN SARANA PRASARANA PEMBELAJARAN - Tyas Kusworowati (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2016)
The purpose of the research is to reveal: 1)Infrastructure of skill lesson, 2) condition oftools and facilities of skill lesson, and 3)creativity of skill teacher in overcoming thelimited of infrastructure facility at SMP Negeri 1Kalibawang. This research uses a qualitativeapproach, activity in qualitative data analysis isdone with an interactive model that is datacollation, data reduction, data presentation andconclusion picture. Methods of data collectionusing interviews, observation, anddocumentation. The results of the studyrevealed: 1) Insufficient facilities for lesson skilllesson, 2) condition of less skilled learninginfrastructure facilities due to old equipment, 3)Teachers have creative attitude demonstrated bythe ability to see problems, find ideas and ideasin learning a skill